Transferring mothers from a free-standing birth center to a reference hospital - Bonadio, Isabel Cristina; Schneck, Camilla Alexsandra; Pires, Luciana Gomes; Osava, Ruth Hitomi; Silva, Flora Maria Barbosa da; Oliveira, Sonia Maria Junqueira Vasconcellos de; Riesco, Maria Luiza Gonzalez (Revista da Escola de Enfermagem da USP, 2011)
The objective of this descriptive study was to characterize the transfers of mothers from the Sapopemba Birth Center to reference hospitals in São Paulo, from September 1998 to July 2008. The studied population was 229 cases of mother transfers. Data were obtained from medical records and record books of the transferred women. Descriptive analysis was performed. The transfer rate was 5.8% (5.5% in the intrapartum period and 0.3% in the postpartum period). Most women who were transferred to the hospital were nulliparous (78.6%). The most common reason for intrapartum transfers was fetal or pelvis abnormalities (22.6%), and abnormal placental detachment (50%) for women in the postpartum period. Some conditions such as nulliparity, cervical dilation at admission, rupture of the membranes and gestational age over 40 weeks were highlighted as important variables for studying the risk factors for mothers being transferred.